Pomegranate and Polyphenolic-rich products Enhance Exercise Performance; General Review - Al-Dujaili, Emad; Bajes, Hana (Jordan Journal of Pharmaceutical Sciences, 2017)
Background: It has been widely accepted that regular exercise represents an important factor to improve health; for the magnificent benefits you can get on the short term and long term. To pave the way for better performance in exercise by improving body strength and reducing risks of muscle injuries, intake of proper nutrients is vital. There are many types of nutrients found in our diets that are all necessary, yet some have additional values. Polyphenols are not only considered for their bioavailability profile, but for their antioxidant properties as well as their diverse beneficial actions1. Aims and objectives: The intent of this review is to provide prevalent information on the effect of polyphenol-rich fruits and polyphenols supplements from different sources on exercise performance. Performance is usually modeled by strength, endurance, and recovery. Conclusions: In consequence demonstrated by several studies presented in this review, polyphenols have been shown to reduce oxidative stress biomarkers, increasing blood flow, increasing O2 gas supply, reducing muscle damage, and therefore improving recovery, endurance, and strength in physically active individuals.